Biochar as amendment to soil growing cassava and water spinach : - Senviset, Outhomphone (Can Tho University, 2017)
Objective: Paper 1:To compare the yeild of sweet and bitter cassava when applying biorchar level from rice husk when peeling and no peeling stems.To compare the soil amendent with different level of biochar addiction.Paper 2:To compare the addition of different biochar sources (rice husk and bamboo) in combination with chicken manure to the soil for growing water spinach . To find the best source and level of biochar addition into the soil amendment and plant growth